Ensuring security the movement of foreign direct investment: Ukraine and the EU economic relations - Trusova, Natalia; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Cherniavska, T.; Kyrylov, Y.; Hranovskа, V.; Skrypnyk, S.; Borovik, L. (My University, 2021)
It is well known that an important positive result of attracting foreign direct investment for the country's economy can be the receipt and subsequent distribution of more advanced production and management technologies. That is why the injection of foreign capital is necessary not only for direct financing but also for the general development of the invested country. The purpose of this article is to consider the theoretical, methodological and practical aspects of ensuring the level of security of investment attractiveness of the world's economies in the polystructural space of foreign direct investment and to highlight the aggregated factors of the investment attractiveness index that characterize the investment climate, investment activity and the state of economic development of the country. To determine the synergistic impact of foreign direct investment on the indicator of the country's investment attractiveness the methods of analysis, synthesis, comparison and mental modelling were used. As a result, it was found that the EU countries are one of the largest investors (the share 65-90% of all investments) in the polystructural space of international investment. It was concluded that in the context of deepening cooperation and realizing the unique capabilities of the states in shaping the global investment climate, it is necessary to ensure a high level of employment of the population by creating new jobs, updating the transfer and introducing the latest technologies, solving social problems at the general level; to carry out an investment modernization of the economy to increase the fixed assets of enterprises; to implement a more effective investment policy.
Keywords: Investment infrastructure; National economy; State's development; Economic growth; International investment